Income Inequality and Poverty among Households Gum Arabic Producers in Sheikan Locality - E.Maruod, Maruod; Ibrahim, Ibrahim Elnour; Tutu, Salih Omer; Abutabaa, Yahia Ibrahim Mohamed; Adam, Hassan Elnour; Elamin, Hatim Mohamed Ahmed; Hamad, Zeinab M. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
The aim of this paper was to assess income inequality and poverty situation among household gum Arabic producers in Sheikan locality. Structured questionnaire using stratified random sampling technique was used to gather households’ poverty data from 13 villages located in three selected districts (Taggat, Umashira and Umsomaima). A total of 300 households representing 10% of population (3002 households) were interviewed. The Foster-Greer-Thorbecke (FGT) measurement, Gini coefficient and Lorenz curve were used to assess poverty incidence, gap, severity and income inequality. Results showed that the poverty incidence, poverty gap and poverty severity were 46%, 32% and 22%, respectively. Also the result of Gini coefficient of gum Arabic income inequality is estimated as 38.5%. To improve household food security, poverty and income equality in North Kordofan state, the study recommends developing of comprehensive capacity building programs for producers (tapping, collection and processing and gum quality); besides availability of sufficient credit sources and credits in time were required for stability of gum sector in the region.